2018
DOI: 10.5539/mas.v12n2p36
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization of Network Arch Bridges with Hollow Tubular Arches and Chords

Abstract: In the framework of bridge engineering, cable structure represent a key argument. The development of innovative bridge solutions are needed in order to keep time and costs at a reasonable level, maintaining at the same time an high level of structural safety and functionality. The network arch bridge solution completely respond to these requirements, and in addition could be designed as a very pleasant and formally elegant structure, because of its slenderness and lightness. In this paper, an introduction on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Tey obtained minimal bending moments at the angle values α � 42-55 °. Similar problems were investigated by Islam Ahsan and Ahsan [15,16], and Pipinato [17,18]. Islam Ahsan showed that circular arch network bridges compared to parabolic arch bridges have a lower arch rise and a lesser number of hangers.…”
Section: Introductionmentioning
confidence: 62%
“…Tey obtained minimal bending moments at the angle values α � 42-55 °. Similar problems were investigated by Islam Ahsan and Ahsan [15,16], and Pipinato [17,18]. Islam Ahsan showed that circular arch network bridges compared to parabolic arch bridges have a lower arch rise and a lesser number of hangers.…”
Section: Introductionmentioning
confidence: 62%
“…In the design process, the stability of steel arch is the key issue. Mostly, linear buckling analysis (LBA) is conducted in the finite elements analysis (FEA) software [2,4,5]. Alternatively, the solution for beam supported by flexible springs is used as a first estimation, especially in optimization tasks, due to its simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…to the appropriate sequence of controls obtained from different conditions. Despite a reach literature published in recent years on the development of arch-shaped optimization [2,8,20,23,25], to the best authors' knowledge these works do not include research in the area of optimal control . The present work is a continuation of the research topic presented in [6].…”
Section: Introductionmentioning
confidence: 99%